2011
DOI: 10.1057/kmrp.2011.1
|View full text |Cite
|
Sign up to set email alerts
|

A study of knowledge management enablers across countries

Abstract: Knowledge has been long cited as a strategic asset and a source of competitive advantage for organizations. However, the creation of knowledge is a complex process that is influenced by several factors beyond the typical practice of knowledge management (KM). In this research, we assess the effects of leadership, Ba (shared context in motion), organizational culture, organizational control, and work style on KM defined in terms of the SECI process of socialization, externalization, combination, and internaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 27 publications
2
31
0
4
Order By: Relevance
“…The general observationisthat knowledge sharing flourishes in less formalised, more decentralised ad-hoc cultures (Tseng, 2010) that foster trust (Holste and Fields, 2010) and entrepreneurial attitude (Suppiah and Sandhu, 2011). At the national level, few researchers conducted comparative KM studies across different countries (Magnier-Watanabe et al, 2011). Others used the cultural dimensions developed by Hofstede et al (1991) and found that knowledge transfer is more prevalent in collectivist than in individualistic cultures (Moss et al, 2007), and is impeded by cultural differences in other dimensions, such as uncertainty avoidance and power distance (Chen et al, 2010, Wang et al, 2011.…”
Section: Managerial and Social Issues In Kmmentioning
confidence: 99%
“…The general observationisthat knowledge sharing flourishes in less formalised, more decentralised ad-hoc cultures (Tseng, 2010) that foster trust (Holste and Fields, 2010) and entrepreneurial attitude (Suppiah and Sandhu, 2011). At the national level, few researchers conducted comparative KM studies across different countries (Magnier-Watanabe et al, 2011). Others used the cultural dimensions developed by Hofstede et al (1991) and found that knowledge transfer is more prevalent in collectivist than in individualistic cultures (Moss et al, 2007), and is impeded by cultural differences in other dimensions, such as uncertainty avoidance and power distance (Chen et al, 2010, Wang et al, 2011.…”
Section: Managerial and Social Issues In Kmmentioning
confidence: 99%
“…TK is subjective and intangible knowledge which is intuitive and difficult to express and practice with language, diagrams, figures, or numbers (Magnier-Watanabe et al, 2011). The term tacit knowledge is originally named by Polanyi (1966).…”
Section: Tacit Knowledgementioning
confidence: 99%
“…It is objective and rational and can be expressed with language, numbers, or formulas. It involves know-how that is transmittable in formal and systematic language and can be stored and disseminated with technology (Crowley, 2000;Nonaka et al, 2001;Magnier-Watanabe et al, 2011;Ekore, 2014). It is easily codified, storable, transferable, and easily expressed and shared (Serban and Luan, 2003).…”
Section: Explicit Knowledgementioning
confidence: 99%
“…They may create new knowledge as a response to the -failures or successes‖ of previous phases. This way, feedback is used to create new knowledge that has been contextualized [1].…”
Section: ) Creatementioning
confidence: 99%
“…Knowledge management can be seen as the set of activities that involve capturing all the best practices and knowledge that people acquire and storing them in a computer system in the hope that one day it will be useful [1]. The term -best practice‖ refers to -those practices that produce superior results; selected by a systematic process; and judged as exemplary, good, or successfully demonstrated‖ [2].…”
Section: Introductionmentioning
confidence: 99%